(3JGL GdYQhS aj TQM GdbGehSs - (3eMeO Hf eMeO Hf eMeO Hf YHO GdQGRb, GdSjO eQJVj GdMSjfj GdRHjOj,CHh GdajV , J (B1205 (3g` s; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s ((3YWaI GdYSGd HeUQ s)
(3ChdgG (B:s
(3CKfGA eGOI (B" (3YQa (B" (3bhdg (B: (3eYQha Hf eScGf (B: (3HCfi GdcYHI eTQagG Gddg JYGdi , CHh GdhdjO Gdeci UOhb ebQi eTghQ , eGJ SfI (B165 (3g` heScGf cYKeGf hbjd HGdcSQ s
(3BNQgG (B:s
(3ChGFd eGOI (B" (3fab (B" (3, bhdg (B: (3fab GdQLd hcPG GdOGHI cGdaQS hGdHZd hSGFQ GdHgGFe bGd TjNfG (B: (3hRGO GHf GdbWGY (B: (3Efg jbGd fabJ s
(3LRA BNQ ef GdfSNI GdChdi HOGQ GdcJH GdeUQjI (B501 (3dZI JjehQ Cs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs